Beyond Walls: Multi-Disciplinary Perspectives: Volume 1: St. Kits and Nevis - Augier, Simone; Edgecombe-Howell, Olivia (The University of the West Indies, School of Continuing Studies, 2002)
The Conference series Beyond Walls: Multi- Disciplinary Perspectives and the first Volume of papers presented at the inaugural conference in St. Kitts and Nevis contribute to the work of the University through research and outreach and strengthen the regional nature of the institution. It looks at 1) National Figures, 2) National Identity and Regionalism, 3) Science and Technology for Development 4) History, Society and Culture, and 5) Educational Development.
Keywords: Multi-disciplinary perspectives